FDI-6 inhibits the expression and function of FOXM1 to sensitize BRCA-proficient triple-negative breast cancer cells to Olaparib by regulating cell cycle progression and DNA damage repair - Shu-Ping Wang; Shi-Qi Wu; Shi-Hui Huang; Yi-Xuan Tang; Liu-Qiong Meng; Feng Liu; Qi-Hua Zhu; Yun-Gen Xu (Cell Death and Disease, 2021)
Abstract Inducing homologous-recombination (HR) deficiency is an effective strategy to broaden the indications of PARP inhibitors in the treatment of triple-negative breast cancer (TNBC). Herein, we find that repression of the oncogenic transcription factor FOXM1 using FOXM1 shRNA or FOXM1 inhibitor FDI-6 can sensitize BRCA-proficient TNBC to PARP inhibitor Olaparib in vitro and in vivo. Mechanistic studies show that Olaparib causes adaptive resistance by arresting the cell cycle at S and G2/M phases for HR repair, increasing the expression of CDK6, CCND1, CDK1, CCNA1, CCNB1, and CDC25B to promote cell cycle progression, and inducing the overexpression of FOXM1, PARP1/2, BRCA1/2, and Rad51 to activate precise repair of damaged DNA. FDI-6 inhibits the expression of FOXM1, PARP1/2, and genes involved in cell cycle control and DNA damage repair to sensitize TNBC cells to Olaparib by blocking cell cycle progression and DNA damage repair. Simultaneously targeting FOXM1 and PARP1/2 is an innovative therapy for more patients with TNBC.